2023
DOI: 10.1371/journal.pone.0284123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminum accumulation on bone and cardiovascular risk in the current era

Abstract: Background The prevalence of aluminum (Al) intoxication has declined over the past 3 decades. However, different groups still report on the diagnosis of Al in bone. Prolonged and low-intensity exposures to Al may not be captured by serum Al measurements, preventing its proper diagnosis. We hypothesize that bone Al accumulation may be related to bone and cardiovascular events in the current Era. Aims To detect the diagnosis of bone Al accumulation; to explore bone and cardiovascular consequences of Al accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
(39 reference statements)
0
6
0
2
Order By: Relevance
“…Este estudo foi realizado como uma subanálise dos dados do REBRABO 5 , e está relacionado, em parte, a dados publicados anteriormente 4,[6][7][8] . A metodologia detalhada foi descrita em outra publicação [4][5][6][7][8] . Em resumo, o REBRABO é uma coorte prospectiva de pacientes com OR.…”
Section: Métodosunclassified
“…Este estudo foi realizado como uma subanálise dos dados do REBRABO 5 , e está relacionado, em parte, a dados publicados anteriormente 4,[6][7][8] . A metodologia detalhada foi descrita em outra publicação [4][5][6][7][8] . Em resumo, o REBRABO é uma coorte prospectiva de pacientes com OR.…”
Section: Métodosunclassified
“…Al is known to inhibit more than 300 biological relevant reactions involving kinases or phosphatases, mostly due to its ability to bind to phosphates [ 79 , 80 ]. It mediates the extra mitochondrial release of free oxygen radicals, resulting in Fe-induced lipid peroxidation and protein denaturation [ 81 , 82 ].…”
Section: Non-essential/toxic Trace Elementsmentioning
confidence: 99%
“…The present study found a DI value of Al in the range of 0.46-0.99 mg from 100 g of sweets (Figure 1). Al is not nutritionally important, and a high concentration may lead to various type of ailments in humans [27,28]. The toxic effects of Al are primarily due to its pro-oxidant activity, which causes oxidative stress, and oxidation of cellular proteins and lipids, ultimately leading to denaturation or conformational or structural alterations.…”
Section: Aluminummentioning
confidence: 99%
“…The toxic effects of Al are primarily due to its pro-oxidant activity, which causes oxidative stress, and oxidation of cellular proteins and lipids, ultimately leading to denaturation or conformational or structural alterations. Exposure to Al has been associated with the development of Alzheimer's disease [27][28][29]. The brain, bones, and kidney are just a few of the many tissues where Al can build up and cause damage and dysfunction.…”
Section: Aluminummentioning
confidence: 99%